PENGELOLAAN POTENSI KELAPA DI KABUPATEN INDRAGIRI HILIR - Setiawan, Hendri; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Abstract            Coconut management in Indragiri Hilir district is very important because it is an excellent potential that can improve the welfare of the community. Based on field observations there are some concerns regarding the potential utilization of the coconuts is not well by farmers, there is no regulation that focuses on managing coconut. The aim of the study is to examine the management of coconuts potential in manner downstream Indragiri Hilir district and any factors that hamper. The concept of the theory used is the Theory of Functions of Management, according to Henry Fayol in (Rohman, 2018). This research method using qualitative research method with case study approach. Data was collected by interview, observation and documentation. These results indicate the management of coconuts Potential in Indragiri Hilir conducted by the Department of Plantation Indragiri Hilir on coconuts are still not optimal because the potential of existing coconut fruit can’t be utilized by the community into a derivative product that has a high economic value. Then the factors that become a obtacles are human resources that are not creative, yet there is no institutional focus on managing coconut management, Lack of budget and no district policy on management. The government of Indragiri Hilir should make a policy governing the management of coconut and make cooperation with coconut processing companies to empower smallholders in making coconut fruit derivative products. Keywords : Management, Potential Of Coconut